Life cycle and description of a new species of Amnestus Dallas (Hemiptera-Heteroptera: Cydnidae) associated with the fruit of several species of Ficus (Moraceae) in Mexico - MARÍA CRISTINA MAYORGA MARTINEZ; LUIS MANUEL CERVANTES PEREDO (Journal of the New York Entomological Society, 2001)
A new species of Amnestus Dallas, A. ficus, is described. Its life cycle, and immature stages are also included and illustrated. The association of Cydnidae with the fruits of various species of Ficus is reported for first time. The study is based mainly on two-year sampling in a small patch of medium rain forest on the coast of Veracruz, combined with records from Chiapas, Guerrero, and San Luis Potosi, Mexico.